The nicotinic receptor of cochlear hair cells: A possible pharmacotherapeutic target? - Elgoyhen, Ana Belen (2009)
Mechanosensory hair cells of the organ of Corti transmit information regarding sound to the central nervous system by way of peripheral afferent neurons. In return, the central nervous system provides feedback and modulates the afferent stream of information through efferent neurons. The medial olivocochlear efferent system makes direct synaptic contacts with outer hair cells and inhibits amplification brought about by the active mechanical process inherent to these cells. This feedback system offers the potential to improve the detection of signals in background noise, to selectively attend to particular signals, and to protect the periphery from damage caused by overly loud sounds. Acetylcholine released at the synapse between efferent terminals and outer hair cells activates a peculiar nicotinic cholinergic receptor subtype, the α9α10 receptor. At present no pharmacotherapeutic approaches have been designed that target this cholinergic receptor to treat pathologies of the auditory system. The potential use of α9α10 selective drugs in conditions such as noise-induced hearing loss, tinnitus and auditory processing disorders is discussed.